Practicing Servant Leadership Developments in Implementation (Springer International Publishing, 2018)
Building on the original writings of Robert K. Greenleaf, this edited collection provides new insights into servant leadership theory and broadens the conceptual framework with a developmental perspective on modern organisations. Bringing together a group of active servant leadership researchers and practitioners from around the world, this book applies Greenleaf's original ideas to current challenges within today's businesses. The authors explore theoretical topics such as purposefulness, compassion, personal growth and mindfulness, as well as providing practical models for implementing a servant leadership culture within organisations, with a particular focus on public administration and the health care industry.